2019
DOI: 10.3389/fimmu.2019.02618
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Antibody Deficiency Due to Monoallelic Alterations in NFKB1

Abstract: Adult-onset primary immunodeficiency is characterized by recurrent infections, hypogammaglobulinemia, and poor antibody response to vaccines. In this study, we have analyzed targeted gene panel sequencing results of 270 patients diagnosed with antibody deficiency and identified five disease-associated variants in NFKB1 in five unrelated families. We detected two single base pair deletions and two single base pair insertions, causing severe protein truncations, and one missense mutation. Immunoblotting, lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 35 publications
6
37
0
Order By: Relevance
“…We concluded, neither the mutant p105 precursor nor the mutant p50, are maintained at high levels in transfected cells (resulting from forced CMV-promoter-driven overexpression) but instead undergo rapid cytoplasmic decay or proteotoxic aggregation within the nucleus, respectively. The subnuclear deposition of severely damaged p50 proteins upon experimental overexpression has previously been observed with other mutations (12,24,34). Severely damaged proteins undergoing enhanced decay, typically gain substantially lower fluorescence signals, which might further decrease over time during the experiment.…”
Section: The Ptyr350cys Missense Change Causes Decay Of Cytoplasmic P105 and Nuclear P50mentioning
confidence: 68%
See 1 more Smart Citation
“…We concluded, neither the mutant p105 precursor nor the mutant p50, are maintained at high levels in transfected cells (resulting from forced CMV-promoter-driven overexpression) but instead undergo rapid cytoplasmic decay or proteotoxic aggregation within the nucleus, respectively. The subnuclear deposition of severely damaged p50 proteins upon experimental overexpression has previously been observed with other mutations (12,24,34). Severely damaged proteins undergoing enhanced decay, typically gain substantially lower fluorescence signals, which might further decrease over time during the experiment.…”
Section: The Ptyr350cys Missense Change Causes Decay Of Cytoplasmic P105 and Nuclear P50mentioning
confidence: 68%
“…Western blotting using isolated PBMCs has successfully been applied to confirm reduced levels of p105 and p50 associated with pathogenic truncating variants, precursor skipping variants and several missense variants ( 12 14 , 22 , 23 , 34 ). EBV-transformed B lymphocytes might be used as an alternative ( 12 , 14 ; Supplementary Figure 3 ), e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the diagnosis of a PID is clear in case the diagnosis of hypogammaglobulinemia precedes immunosuppressive treatment of autoimmune or lymphoproliferative conditions. However, autoimmunity or lymphoproliferative disease and introduction of immunosuppressive treatment could precede the diagnosis of hypogammaglobulinemia [8][9][10][11][12]. The relatively recent discovery of monogenic disorders manifesting as CVID and subsequent studies of cohorts of patients with common monogenic defects revealed that hypogammaglobulinemia in primary immunodeficiency may have a later onset than autoimmunity or lymphoproliferative disease, which can phenotypically prevail [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with NFκB1 haploinsufficiency there is a wide phenotypic spectrum with variable expressivity even within the same family unit (10). Clinical presentations may include recurrent infections, autoimmune disease, and malignancy; in particular, Evans Syndrome (ES) should trigger concern for NFkB1-related disease (11)(12)(13). Notably, the phenotypic features continue to evolve as a description of recurrent necrotizing cellulitis following a dental procedure has just been described within the spectrum of NFkB1 deficiency (14).…”
Section: Introductionmentioning
confidence: 99%